Natural Field Infestation of Mangifera casturi and Mangifera lalijiwa by Oriental Fruit Fly, Bactrocera dorsalis (Diptera: Tephritidae). (14th July 2017) - McQuate, Grant T; Sylva, Charmaine D; Liquido, Nicanor J
Mango, Mangifera indica (Anacardiaceae), is a crop cultivated pantropically. There are, however, many other Mangifera spp ("mango relatives") which have much more restricted distributions and are poorly known but have potential to produce mango-like fruits in areas where mangoes do not grow well or could be tapped in mango breeding programs. Because of the restricted distribution of many of the Mangifera spp, there has also been limited data collected on susceptibility of their fruits to infestation by tephritid fruit flies which is important to know for concerns both for quality of production and for quarantine security of fruit exports. Here, we report on natural field infestation by the oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae), of two mango relatives native to Indonesia: Mangifera casturi and Mangifera lalijiwa . Rates of infestation of fruits of these two Mangifera spp by tephritid fruit flies have not previously been reported.